Mitigation of urban voids in traditional neighborhoods: The case of the Al-Najada zone in Doha, Qatar - Asmaa Saleh, AL-Mohannadi (2023)
Urban voids and leftover spaces challenge the urban development of cities and result in land vacancy and other spatial planning issues. Such spaces have great potential for innovative intervention through piece-by-piece sustainable urban design and small-scale actions to foster livability and sustainability. This paper analyzes urban voids in the Al-Najada zone in Doha, Qatar. The zone has a valuable cultural and historical background. The paper uses the case study method to analyze the urban voids and develop re-planning scenarios through visual schematic design and photomontage. The paper demonstrates the application of sustainable and social principles to rejuvenate old areas by creating functions for urban voids.